Characteristics of sea surface current during the second transitional monsoon in the Bangka strait, North Sulawesi, Indonesia - Kusumawardani, Niken; Djamaluddin, Rignolda; Angmalisang, Ping Astony; Manu, Lusia; Pelle, Wilmy Etwil (JASM, 2024)
Understanding the dynamics of surface currents in the Bangka Strait is crucial for various maritime and coastal activities. This strait connects Likupang, a super-priority tourism destination, with other islands in North Sulawesi. These activities include navigation safety, inter-island transportation, fisheries, search and rescue operations, and marine pollution control. This study investigated the characteristics of currents in the strait using a hydrodynamic model called Delft3D. The result revealed that the currents exhibit a tidal pattern, with dominant westward flow during floods and eastward flow during ebb. Maximum sea current velocity during spring tide in the second transition monsoon occurred in September 2022, with an average speed of 102.67 cm/s. Current ellipse analysis confirmed the tidal type of the currents.